(untitled) (Research, Society and Development, 2023)
Objective: To carry out an integrative literature review about the work of the multidisciplinary health team in Brazilian socio-educational units. Methodology: This is an integrative literature review carried out between June and July 2023 in the SciELO and Virtual Health Library databases by crossing the descriptors “Adolescent, Institutionalized”, “Health of Institutionalized Adolescents”, “Adolescent Health Services” and “Patient Care Team”. As inclusion criteria, studies were accepted in full, in Portuguese, English and Spanish, and duplicate works that did not meet the proposed theme were excluded. Results: After applying the inclusion and exclusion criteria, six studies were selected for the review, which generated two thematic islands for discussion: (1) the multidisciplinary team as a care tool in the socio-educational system and (2) mental health as performance scenario of the multidisciplinary team. Conclusion: The work of the multiprofessional health team is essential for the daily care of these adolescents, and publications that reflect the work carried out in socio-educational units should be encouraged, especially with emphasis on the practice of these teams.